Synthesization and Characterization of the N-substituted Tetrahydrocarbazole Compounds by Molecular Docking Method - Padmavathi, Sakinala; Bhadramaraju, Ramu; Uddoju, Mamatha; Venkataramana, Nosina; Tajne, Madhukar Rajaram; Supriya, Illuri (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
The objective of the study was to synthesize and characterize the N-substituted tetrahydrocarbazole compounds, along with molecular docking studies of the synthesized compounds associated with the evaluation of anti-bacterial activity by the agar cup method. Drug design, often referred to as rational drug design or simply rational design, is the inventive process of finding new medications based on the knowledge of a biological target. The heterocyclic compounds named tetrahydrocarbazoles have significant biological properties. The recently created substituted tetrahydrocarbazole compounds were made by refluxing substituted cyclohexanone and phenylhydrazine in glacial acetic acid. These intermediates were ultimately transformed into N-substituted tetrahydrocarbazoles through a reaction with substituted aromatic acid chlorides in alkaline conditions. Fifteen compounds are synthesized and characterized by their melting point (MP), IR, NMR, MS, and elemental analysis. All the compounds were subjected to molecular docking studies for Gln-6-p enzyme (1XFF) inhibition. The newly synthesized tetrahydrocarbazole derivatives were studied for anti-microbial activity using the agar cup method. In silico studies revealed that all the synthesized compounds have relatively better binding affinity as compared to the standard drug. So, it may be considered a good inhibitor of GlcN-6-P. The anti-microbial activity was assessed by the agar cup plate method, and the results showed eight compounds having a better anti-microbial response against the bacterial and fungal strains. The study helps to expand the scope of developing these tetrahydrocarbazole derivatives, which help to promote effective anti-bacterial agents.